Multimodal Imaging of Substantia Nigra in Parkinson's Disease with Levodopa‐Induced Dyskinesia - Su, Dongning; Gan, Yawen; Zhang, Zhe; Cui, Yusha; Zhang, Zhijin; Liu, Zhu; Wang, Zhan; Zhou, Junhong; Sossi, Vesna; Stoessl, A. Jon; Wu, Tao; Jing, Jing; et al. (Movement disorders, 2023)
Background Degeneration of the substantia nigra (SN) may contribute to levodopa‐induced dyskinesia (LID) in Parkinson's disease (PD), but the exact characteristics of SN in LID remain unclear. Objective To further understand the pathogenesis of patients with PD with LID (PD‐LID), we explored the structural and functional characteristics of SN in PD‐LID using multimodal magnetic resonance imaging (MRI). Methods Twenty‐nine patients with PD‐LID, 37 patients with PD without LID (PD‐nLID), and 28 healthy control subjects underwent T1‐weighted MRI, quantitative susceptibility mapping, neuromelanin‐sensitive MRI, multishell diffusion MRI, and resting‐state functional MRI. Different measures characterizing the SN were obtained using a region of interest–based approach. Results Compared with patients with PD‐nLID and healthy control subjects, the quantitative susceptibility mapping values of SN pars compacta (SNpc) were significantly higher (P = 0.049 and P = 0.00002), and the neuromelanin contrast‐to‐noise ratio values in SNpc were significantly lower (P = 0.012 and P = 0.000002) in PD‐LID. The intracellular volume fraction of the posterior SN in PD‐LID was significantly higher compared with PD‐nLID (P = 0.037). Resting‐state fMRI indicated that PD‐LID in the medication off state showed higher functional connectivity between the SNpc and putamen compared with PD‐nLID (P = 0.031), and the functional connectivity changes in PD‐LID were positively correlated with Unified Dyskinesia Rating Scale total scores (R = 0.427, P = 0.042). Conclusions Our multimodal imaging findings highlight greater neurodegeneration in SN and the altered nigrostriatal connectivity in PD‐LID. These characteristics provide a new perspective into the role of SN in the pathophysiological mechanisms underlying PD‐LID. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.